Iron Jawed angels - Von Garnier, Katja (HBO Films, 2004)
Taking a french and contemporary look at pivotal event in American history, IRON JAWED ANGELS tells the true story of how defiant and brilliant young activists Alice Paul, played by Hilary Swank (Boys Don't Cry, Insomnia), and Lucy Burns, played Frances O' Connor (Windtalkers, Artificial Intelligence:All), took the women's suffrage movement by storm, putting their lives at risk to help American women in the right to vote